(untitled) (LEARNing Landscapes, 2009)
As we encourage creativity in curriculum, we often forget that the whole agenda is made up. Creativity is the foundation of all knowledge and all curriculum. In this essay I argue that teachers do not need to be more creative, but do need to participate in the politics that will diminish our subordination. Because the creativity of the corporation and the testing companies has swamped the creativity of the classroom, the current economic crisis may provide opportunities for teachers to reassert the authority of our imaginations.